Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan di Four Star By Trans Hotel Renon - Dewi, Kadek Ayu Arista; Mekarini, Ni Wayan; Putri , Komang Shintiya Nita Kristiana (Jurnal Mosaik Hospitaliti, 2022)
The purpose of this research is to determine the influence of the work environment and compensation on employee performance at Four Star by Trans Hotel. The respondents in this study were 70 employees who worked at Four Star by Trans Hotel. Data collection was carried out by means of surveys, observations, interviews and documentation. This research uses quantitative descriptive data analysis to see the linear relationship between the work environment, compensation and employee performance using SPSS software. The results of this research are first, the work environment partially has a positive and significant effect on employee performance at Four Star by Trans Hotel Bali; second, partial compensation has a positive and significant influence on employee performance at Four Star by Trans Hotel Bali; third, the work environment and compensation simultaneously have a positive and significant effect on employee performance at Four Star by Trans Hotel Bali. The conclusion of this research is that improving the work environment and compensation will improve employee performance.